Abdominal cocoon: preoperative diagnosis on CT. Issue 5 (31st May 2019) - Mohakud, Sudipta; Juneja, Aparna; Lal, Hira
Abstract : A 23-year-old man presented to the emergency department with a history of recurrent episodes of subacute intestinal obstruction. Palpation revealed a firm, non-tender, mobile, non-pulsatile mass of size 8–10 cm with indistinct margins and smooth surface in the hypogastrium. Contrast-enhanced CT scan of the abdomen showed clumping of the small bowel loops within a well-defined membrane-like structure without dilatation or thickening of bowel loops. The patient underwent a laparotomy with incision of the membrane and separation of all the small bowel loops inside the cocoon. Abdominal cocoon is the idiopathic variety of sclerosing encapsulating peritonitis and is an unusual cause of acute or subacute intestinal obstruction. Clinical diagnosis is difficult because of non-specific symptoms. CT has facilitated accurate preoperative diagnosis, long before the patient presents with full-fledged symptoms of acute intestinal obstruction. CT scan plays a significant role in excluding the secondary causes and helps in patient management.